FLIP-CLASSROOM ENGLISH MATERIAL DESIGN FOR POST PANDEMIC PRACTICES TO PROVISION READING LITERACY SKILL - Nina Fatriana (English Journal Literacy Utama, 2021)
Anticipating the post pandemy of 2021/2022, vocational school should design its curriculum as the flip classroom due to its favorablilities: maintaining the online learning circumstances and habituating students with learning autonomy and Bloom’s cognitive level practices in that students pre read at home and learn collaboratively at school through either the applying stage at the least, or the higher stage of PBET, PJBL or PBL. This condition challenges teachers to design the materials and activities for pre and in class respectively. This paper proposes English flip classroom design for students at vocational school to habituate them to read online at home (habituating students’ autonomy at Bloom’s LOTS- remembering and understanding) and to perform collaboration through PBET, PJBL, or PBL (habituating students with Bloom’s MOTS-HOTS- applying, analyzing, evaluating and creating) to result in the formation of reading literacy skill to face the AKM at 11 grades.